2019
DOI: 10.1371/journal.pone.0211553
|View full text |Cite
|
Sign up to set email alerts
|

Viral infection detection using metagenomics technology in six poultry farms of eastern China

Abstract: With rapidly increasing animal pathogen surveillance requirements, new technologies are needed for a comprehensive understanding of the roles of pathogens in the occurrence and development of animal diseases. We applied metagenomic technology to avian virus surveillance to study the main viruses infecting six poultry farms in two provinces in eastern China. Cloacal/throat double swabs were collected from 60 birds at each farm according to a random sampling method. The results showed that the method could simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, DHBV has been reported to not only infect ducks but also to cause some diseases in geese (Funk et al, 2007 ). The infection rate of DHBV is very high in eastern China based on avian virus surveillance (Qiu et al, 2019 ). The characteristics of DHBV call for increased attention to related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, DHBV has been reported to not only infect ducks but also to cause some diseases in geese (Funk et al, 2007 ). The infection rate of DHBV is very high in eastern China based on avian virus surveillance (Qiu et al, 2019 ). The characteristics of DHBV call for increased attention to related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…From 2009 to 2017 almost 20 animal and zoonotic viral disease agents were diagnosed using metagenomic technique (Hoeper et al, 2017). A limited scale metagenomics-based pathogen surveillance study on 6 poultry farms detected the main infectious viruses of poultry, and it analyzed Indian Journal of Animal Health, Special Issue, December, 2020 the subtypes, genotypes and pathogenicity of some detected viruses (Qiu et al, 2019). Subsequent to the metagenomic investigation of astroviruses in enteric disorders in humans (Finkbeiner et al, 2009), a divergent strain was demonstrated to be associated with the brain tissue of shaking mink syndrome affected minks (Blomström et al, 2010).…”
Section: Metagenomics In Diagnosismentioning
confidence: 99%
“…Several approaches have been employed to study the epidemiology of viral infections affecting poultry, including pathogen surveillance and tracking the molecular epidemiology of pathogens [12]. Previous methods employed polymerase chain reaction (PCR)-based methods, especially reverse transcription PCR [12]. Using this strategy, several viruses have been implicated in poultry diseases, including astroviruses [13], parvoviruses [14], reoviruses [15], rotaviruses [16], paramyxoviruses [17], and coronaviruses [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, metagenomics-based detection methods are being applied successfully to characterize viral populations in different hosts and environments [20]. This has facilitated the discovery of many novel viral agents from different types of tissues, including the gastrointestinal tract and the oral-pharyngeal regions in poultry and other livestock [12,[20][21][22][23][24][25]. The popularity of these techniques is largely due to their high sensitivity and wide coverage as they target the entire genome [12,25].…”
Section: Introductionmentioning
confidence: 99%